Bronzens usynlige farver - Bøgh Jensen, Simone (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
This paper presents a study of the use of colours in bronze jewellery and decorative ornaments from Denmark's late Bronze Age" (around 1100-500 BC). These analyses result in a more detailed knowledge of the bronzesmiths’ production of bronze artifacts. Based on previous research on possible colours of tin-bronzes, the colours are divided into five groups: red, orange, golden, silver, and tinned. XRF-analyses are used to determine the chemical composition of the chosen artifacts, thus making it possible to estimate the original colours of the bronzes used. Based on this, it is possible to recognize certain tendencies in specific artifact groups, such as the tutuli, which have mostly been produced in a golden colour and within a different range of 3 % in tin content. Furthermore, two possible options to produce artifacts in a chosen colour are presented by applying the theories about the bronzesmith and this person’s skills and knowledge. Thiis study shows the perspective of future research on the colours in bronze artifacts from the bronze age.